Application of Nanotechnology in Food Science: Perception and Overview - Singh, Trepti; Shukla, Shruti; Kumar, Pradeep; Wahla, Verinder; Bajpai, Vivek K.; Rather, Irfan A. (Frontiers in Microbiology, 2017)
Recent innovations in nanotechnology have transformed a number of scientific and industrial areas including the food industry. Applications of nanotechnology have emerged with increasing need of nanoparticle uses in various fields of food science and food microbiology, including food processing, food packaging, functional food development, food safety, detection of foodborne pathogens and self-life extension of food and/or food products. This review summarizes the potential of nanoparticles for their uses in the food industry in order to provide consumers a safe and contamination free food and to ensure the consumer acceptability of the food with enhanced functional properties. Aspects of application of nanotechnology in relation to increasing in food nutrition and organoleptic properties of foods have also been discussed briefly along with a few insights on safety issues and regulatory concerns on nano-processed food products.